2011
DOI: 10.1007/s00467-011-1977-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with acute kidney injury in extremely low birth weight (ELBW) infants

Abstract: The aim of this study was to determine the incidence, risk factors, and outcome of acute kidney injury (AKI) in extremely low birth weight (ELBW) infants. In a case-control study, medical records of all ELBW infants who were admitted to our Neonatal Intensive Care Unit (NICU) between 1 January 2000 and 31 January 2008 were reviewed. During the study period, 12.5% (59/472) of all ELBW infants developed AKI. Forty-six infants with available medical records were matched to 46 controls. The mean gestational age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 39 publications
(75 reference statements)
7
68
2
1
Order By: Relevance
“…After adjusting for potential confounders, those with AKI had a significantly higher chance of death (hazard ratio 2.4, 95% confidence interval [CI] 0.95-6.0; P , .06). Viswanathan et al 65 reported similar findings in a retrospective singlecenter study, where 12.5% (59/472) of all ELBW infants developed AKI and mortality among those with AKI was significantly higher than controls (70% vs 22%, respectively). In a large retrospective study of VLBW infants, Carmody et al 66 examined 455 VLBW infants and found an AKI incidence of 39.8%.…”
Section: Vlbw and Elbw Neonatessupporting
confidence: 54%
See 1 more Smart Citation
“…After adjusting for potential confounders, those with AKI had a significantly higher chance of death (hazard ratio 2.4, 95% confidence interval [CI] 0.95-6.0; P , .06). Viswanathan et al 65 reported similar findings in a retrospective singlecenter study, where 12.5% (59/472) of all ELBW infants developed AKI and mortality among those with AKI was significantly higher than controls (70% vs 22%, respectively). In a large retrospective study of VLBW infants, Carmody et al 66 examined 455 VLBW infants and found an AKI incidence of 39.8%.…”
Section: Vlbw and Elbw Neonatessupporting
confidence: 54%
“…10,65,66 In 2011, Koralkar et al 10 reported on 229 VLBW infants followed prospectively from birth until 36 weeks postmenstrual age. The incidence of AKI, by using the neonatal modified KDIGO criteria, was 18%.…”
Section: Vlbw and Elbw Neonatesmentioning
confidence: 99%
“…Retrospective studies have been undertaken to assess the prevalence and the clinical and biochemical features of AKI following clindamycin treatment (6)(7)(8). AKI related to the administration of clindamycin is generally associated with oligoanuria, the same as in our patient.…”
Section: Discussionmentioning
confidence: 87%
“…However, in most cases, the incidence of major morbidities has changed very little, especially for extremely premature infants (1,2). Acute kidney injury (AKI), indicated by a rise in serum creatinine (SCr) occurs in approximately 12-18% of preterm neonates (3). Premature infants typically have immature renal structure and function at birth, are often exposed to nephrotoxic medications and are at high risk of AKI in the perinatal period.…”
mentioning
confidence: 99%